Internet connectivity disruption in Malaysia (Malaysia) - Voidly (2026)
CRITICAL severity mixed detected in Malaysia. Confidence: 67%. Data sourced from IODA, CensoredPlanet.
Censorship Incident ID: MY-2026-0028
Keywords: censorship; MY; mixed; critical